PENGARUH KEBIJAKAN PERPAJAKAN, ADMINISTRASI PERPAJAKAN, TARIF PAJAK DAN LOOPHOLES TERHADAP MOTIVASI MANAJEMEN DALAM MELAKUKAN TAX PLANNING (Studi Empiris Pada Wajib Pajak Badan Yang Terdaftar di KPP Pratama Pekanbaru Senapelan) - Agneza, Putri; Tanjung, Amries Rusli; Hasan, Mudrika alamsyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
the research aims to examine The Influence of tax policy, tax administration, tax rates and loopholes to the motivation of the management company in tax planning. Object of this research is company that registered as a taxpayer in KPP Pratama Pekanbaru Senapelan. There are sixty questionnaires were sent, but only forty seven questionnaires are returned. That data are analyzed by linear regression method and SPSS program version 19. The variables were examined are Influence of tax policy, tax administration, tax rates and loopholes to the motivation of the management company in tax planning, The results of this research showed that tax policy has no effect to the motivation of the management company in tax planning with 0,061 significance, the tax administration has no effect to the motivation of the management company in tax planning with 0,009 significance, tax rates has an effect to the motivation of the management company in tax planning with 0,006 significance and loopholes has an effect to the motivation of the management company in tax planning with 0,004 significance. The results of this research also showed that coefficient R square is 70,1%. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well. While the remaining influenced by other variables not included in the regression models were not included in this study as tax regulation or administration punishment. All variables also have strong relation with variable dependents in this research.Keywords: tax policy, tax administration, tax rates, loopholes and the motivation of the management company in tax planning